Humanitarian intervention and the protection of civilian populations - Badmus Isiaka Alani (Međunarodni Problemi, 2009)
The author interrogates the critical question of whether forcible humanitarian intervention be legitimised in spite of clear contradiction to the classical norms of inter-state relations. Classical approach puts emphasize on the principle of sovereignty when governments become the perpetrators of human rights abuses of their citizens, or if states have collapsed into civil war, chaos, and disorder. The author examines this security debate by juxtaposing the age-old doctrine of humanitarian intervention vis-à-vis the imperatives of the concept of ' Responsibility to Protect'. The author argues that humanitarian intervention, due to the ambiguities and controversies surrounding its application, has become an anachronism, which ultimately led to the conceptualisation of Responsibility to Protect vulnerable populations. This approach is based on its concerns with human security as against that of the state and its relevance as arbiter to the longstanding discord between sovereignty and intervention.